The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/gps.4266
|View full text |Cite
|
Sign up to set email alerts
|

The association between higher social support and lower depressive symptoms among aging services clients is attenuated at higher levels of functional impairment

Abstract: Objective Adults seeking services from the Aging Services Provider Network (ASPN) are at risk for depression. ASPN clients also have high prevalence of both functional impairments and social morbidities. Study of the relationships between these factors may inform the development of interventions for depression in this service setting. Methods We interviewed 373 older adults accessing ASPN services and assessed depression symptom severity, functional impairment (instrumental activities of daily living and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Among HCBS recipients, over a quarter (27%) had, in the past year, reported clinically meaningful depressive symptoms, a two-fold greater frequency compared to non-recipients. These findings are consistent with local studies such as a report of HCBS recipients in Monroe County, NY, which found 27% of participants met criteria for major depressive episode (1, 25). The current study finds relatively higher levels of depressive symptoms, however, than found in community-area studies of home delivered meal recipients.…”
Section: Discussionsupporting
confidence: 91%
“…Among HCBS recipients, over a quarter (27%) had, in the past year, reported clinically meaningful depressive symptoms, a two-fold greater frequency compared to non-recipients. These findings are consistent with local studies such as a report of HCBS recipients in Monroe County, NY, which found 27% of participants met criteria for major depressive episode (1, 25). The current study finds relatively higher levels of depressive symptoms, however, than found in community-area studies of home delivered meal recipients.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with findings demonstrating that depression and low social support are associated with suicidal ideation and suicide risk in older adults [36, 37, 38]. The effect of both treatments on reducing suicidal ideation in patients with low social support compared to patients with high social support may reflect a floor effect as rates of suicidal ideation were lower in participants with high social support.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Vietnamese elderly are exposed to less social interactions due to the limited social activities held by the local authority as compared to other developed countries [6]. Elderly with lower levels of social support are more likely to be physically inactive [38], depressed [36,39,40], which are reported to be closely related to FoF [18,41]. In addition, we found that the mean MMSE score of the participants with low-moderate perceived social support levels was 25.5, which was significantly lower than that of those with a high perceived level of social .…”
Section: Cognitive Impairment and Fof Among Different Perceived Sociamentioning
confidence: 99%